2016
DOI: 10.1016/j.phrs.2016.09.033
|View full text |Cite
|
Sign up to set email alerts
|

The thiirane-based selective MT1-MMP/MMP2 inhibitor ND-322 reduces melanoma tumor growth and delays metastatic dissemination

Abstract: MT1-MMP and MMP2 have been implicated as pro-tumorigenic and pro-metastatic factors in a wide variety of cancers including melanoma. We have previously demonstrated that MT1-MMP is highly expressed in melanoma where it promotes melanoma cell invasion and metastasis in part through the activation of its target MMP2. Given the accessibility of MMPs, as they are either secreted (e.g. MMP2) or membrane-tethered (e.g. MT1-MMP), they represent ideal targets for specific inhibition via small molecules. Here we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…For instance, specific inhibition of either MMP-2 or MT1-MMP by specific shRNAs hampers melanoma cell migration and invasion. 63 Gene therapy has shown some success in animal models, and with the design of efficient and safe gene delivery into target tissues downregulation of MMPs using siRNA or overexpression of TIMPs may have clinical applications. 64 …”
Section: Other Biological and Pleiotropic Inhibitors Of Mmpsmentioning
confidence: 99%
“…For instance, specific inhibition of either MMP-2 or MT1-MMP by specific shRNAs hampers melanoma cell migration and invasion. 63 Gene therapy has shown some success in animal models, and with the design of efficient and safe gene delivery into target tissues downregulation of MMPs using siRNA or overexpression of TIMPs may have clinical applications. 64 …”
Section: Other Biological and Pleiotropic Inhibitors Of Mmpsmentioning
confidence: 99%
“…And knockdown of RGS4 activated melanoma cell migration and invasion; also degradation of RGS4 increased the expression of MMPs. In addition, it has been validated that MMP2 and MMP9 are implicated in the development and metastasis of cutaneous melanoma [ 44 , 45 ]. Several evidences indicated that CXCR4/SDF1 promoted prostate cancer cell invasion through MMP9 activation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, MT-MMPs and MMP-2 cooperate in the invasive and metastatic process of melanoma cells [123]. Recent research also showed that effective inhibition of MT1-MMP and MMP2 can effectively reduce melanoma cell growth, migration and invasion in vitro [148]. in primary melanoma patients who received adjuvant immunotherapy.…”
Section: Mt-mmpsmentioning
confidence: 99%